Hysteresis in Oil Flow through a Rotating Tube with Twin Exit Branches - Sun-Wen Cheng; Wen-Jei Yang (International Journal of Rotating Machinery)
Oil enters a horizontal rotating tube through a radially-attached duct at one end. The tube with the other end closed is attached with radial twin exit branches permitting oil to exit into open air. Air begins to enter through one of the two branches into the tube when its rotational speed reaches certain critical values. An experimental study is performed to investigate this air-oil two-phase flow behavior. Both the tube and the branches are transparent to allow illumination and flow visualization during spin-up and spin-down processes. The branch-totube diameter ratio, rotational speed, and oil flow rate are varied. Changes in oil flow rates are measured as a function of rotational speed. A comparison is made between cases of a varying total oil flow rate due to rotation effects and a constant one under control. It is disclosed that cavitation in oil flow is induced by air entering the branches opposite to the ejecting oil flow. Subsequently air bubbles progress in the tube. The origin of this intrusion depends on the hydraulic head loss of the piping system. This study can be applied to oil lubrication analysis of rotating machinery, such as automotive transmission lines.